PENINGKATAN PENGUASAAN KOSAKATA BAHASA INGGRIS DENGAN MEDIA FILM PENDEK PADA SISWA MIS UNGGULAN MASJID BESAR JABALUL KHOIR PURWODADI - Wahyu Unggul Widodo; Endang Susilowati; Khoirotun Nisa; Putri Isna Fatmawati; Roisa Nur Wakhidah; Dian Oktaviani (Jurnal Pengabdian kepada Masyarakat Cahaya Negeriku, 2025)
Background : English is an international language used in various fields. It is one of the languages that is considered important to learn in the current era of globalization. It is important to develop English language skills from an early age. One of the skills that really needs to be trained from an early age is mastery of English vocabulary. Without sufficient vocabulary, a person cannot communicate effectively and cannot express his ideas well in oral or written form. Uninteresting teaching methods, false beliefs about the relationship between language and everyday life, and social and cultural environments that influence students' attitudes towards learning English are some of the many causes of low interest in learning English. Currently, there are many interactive and interesting digital English learning media that can help students learn English more effectively.   Methodology : The methods used in this activity were asking the students to watch a short film, then gave them questions related to the vocabulary in the film and trained the students to use the vocabulary in other contexts.   Result : After watching the film and being giving explanation, students are able to arrange sentences with the given vocabularies.   Conclusion : The use of short films to help students improve vocabulary mastery is very effective. This is because in learning students feel entertained by watching short films, so they learn with a happy mood. In addition, the vocabulary displayed in short films helps students get visualization and examples of vocabulary use with real applications through short films.